The Negative Effects of Biochar on Soil, Water, Plants, the Environment and Human Health - Sainath, N.; Ramanjaneyulu, A. V.; Rajanikanth, E.; Kumar, R. Sai; Venugopal, G.; Chaitanya, T. (Chronicle of Bioresource Management, 2025)
Biochar, a carbon-rich product derived from biomass pyrolysis, has been widely promoted for it’s potential benefits in soil improvement, carbon sequestration and pollution mitigation. However, recent studies have raised concerns about it’s negative impacts on soil health, water quality, plant growth, human health and overall environmental stability. This article explores the potential drawbacks of biochar application, emphasizing it’s role in altering soil microbial communities, water retention, plant toxicity, human exposure risks and it’s unintended ecological consequences.